1986
DOI: 10.2136/sssaj1986.03615995005000050024x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acidity on Nitrogen Mineralization and Nitrification in Atlantic Coastal Plain Soils

Abstract: The objective of this study was to determine the effect of acidity on mineralization, nitrification, and N2O evolution during these processes on naturally acid soils from the lower Coastal Plain of North Carolina. Six acid surface soils (pH ≤4.5) from the Tidewater region of North Carolina, with a range of organic matter (OM) contents (28‐850 g kg−1) were limed to give a range of pH values so that the effect of acidity on mineralization of organic N and nitrification of (NH4)2SO4 could be studied under control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…It is well known that low pH decreases the activity of the N 2 O-reductase, thereby increasing production of N 2 O from denitrification (Nömmik, 1956;Weier and Gillam, 1986;Granli and Bockman, 1994). For nitrification, it has also been demonstrated that low pH values favor N 2 O production (Sitaula and Bakken, 1993;Martikainen and De Boer, 1993;Kesik et al, 2006).…”
Section: Claymentioning
confidence: 99%
“…It is well known that low pH decreases the activity of the N 2 O-reductase, thereby increasing production of N 2 O from denitrification (Nömmik, 1956;Weier and Gillam, 1986;Granli and Bockman, 1994). For nitrification, it has also been demonstrated that low pH values favor N 2 O production (Sitaula and Bakken, 1993;Martikainen and De Boer, 1993;Kesik et al, 2006).…”
Section: Claymentioning
confidence: 99%
“…Nitrification has, however, been reported in acid soils at pH values as low as 3.7 (5,9,11,25,26,34,35,37). Although this may be due, in some cases, to heterotrophic nitrification (1,22) there is strong evidence for autotrophic nitrification in acid soils (19,38). Autotrophic ammonia oxidizers have been isolated from and enumerated in acid soils (7,13,16,20,26) and 16S rRNA gene sequences of ammonia oxidizers are frequently detected (6,33), with evidence for changes in relative abundance of different sequence clusters in soils of different pH (32).…”
mentioning
confidence: 99%
“…Soils with pH value below 4.5 were observed to nitrify (Weber and Gainey 1962;Weier and Gilliam 1986) probably by acid adapted strains. Soil pH was insignificantly correlated with nitrifiers population, in contrast to the frequently reported negative relationship between pH and nitrifiers population (Dancer et al 1973;Gilmour 1984).…”
Section: Resultsmentioning
confidence: 99%